Conservation tillage practices affect soil microbial diversity and composition in experimental fields - Khan, Muzammil Hassan; Liu, Hao; Zhu, Anning; Khan, Mudassir Hassan; Hussain, Sarfraz; Cao, Hui (Frontiers in Microbiology, 2023)
Conservation tillage is a widely used technique worldwide, but the effects of conservation tillage on bacterial community structure are poorly understood. We explored proportional alterations in the bacterial community under different tillage treatments. Tillage treatments included tillage no-straw retention (CntWt), no-tillage with straw retention (CntWntS), tillage with straw retention (CntWtS), no-tillage and no-straw retention (CntWnt). The influence of tillage practices on soil bacterial communities was investigated using Illumina MiSeq sequencing. Different tillage methods and straw retention systems significantly influenced soil parameters such as total potassium and pH were not affected by tillage practices, while straw retention significantly affected soil parameters including nitrogen content, available phosphorus and available potassium. Straw retention decreased bacterial diversity while increased bacterial richness. The effect of straw retention and tillage on bacterial communities was greater than with no tillage. Phylogenetic β-diversity analysis showed that deterministic homogeneous selection processes were dominated, while stochastic processes were more pronounced in tillage without straw retention. Ecological network analysis showed that microbial community correlation was increased in CntWntS and CntWnt. Straw retention treatment significantly increased the relative abundance of bacterial taxa Proteobacteria, Bacteroidetes, and OD1, while Nitrospirae, Actinobacteria, and Verrucomicrobia significantly decreased. The conservation tillage practices significantly affect soil properties, bacterial composition, and assembly processes; however, further studies are required to investigate the impact of different crops, tillage practices and physiological characteristics on bacterial community structure and functions.